A Call to liberation - "Chidananda, Swami" (Tehri-Garhwal, 1997)
Swami Chidanandaji,successor to Swami Sivananda is well known for his morning meditation talks. Seekers through out the world will find within this book answers to many of their un-resolved questions. Seekers all over the world will probably compare Divine Life Society to an "artesian well" ever quenching the thirst of the spirtual seeker.Draw from it and be benefitted.
Keywords: Liberation